Generation of insulin-producing cells from the mouse liver using β cell-related gene transfer including Mafa and Mafb. - Haruka Nagasaki; Tokio Katsumata; Hisashi Oishi; Pei-Han Tai; Yukari Sekiguchi; Ryusuke Koshida; Yunshin Jung; Takashi Kudo; Satoru Takahashi (PLoS ONE, 2014)
Recent studies on the large Maf transcription factors have shown that Mafb and Mafa have respective and distinctive roles in β-cell development and maturation. However, whether this difference in roles is due to the timing of the gene expression (roughly, expression of Mafb before birth and of Mafa after birth) or to the specific function of each gene is unclear. Our aim was to examine the functional differences between these genes that are closely related to β cells by using an in vivo model of β-like cell generation. We monitored insulin gene transcription by measuring bioluminescence emitted from the liver of insulin promoter-luciferase transgenic (MIP-Luc-VU) mice. Adenoviral gene transfers of Pdx1/Neurod/Mafa (PDA) and Pdx1/Neurod/Mafb (PDB) combinations generated intense luminescence from the liver that lasted for more than 1 week and peaked at 3 days after transduction. The peak signal intensities of PDA and PDB were comparable. However, PDA but not PDB transfer resulted in significant bioluminescence on day 10, suggesting that Mafa has a more sustainable role in insulin gene activation than does Mafb. Both PDA and PDB transfers ameliorated the glucose levels in a streptozotocin (STZ)-induced diabetic model for up to 21 days and 7 days, respectively. Furthermore, PDA transfer induced several gene expressions necessary for glucose sensing and insulin secretion in the liver on day 9. However, a glucose tolerance test and liver perfusion experiment did not show glucose-stimulated insulin secretion from intrahepatic β-like cells. These results demonstrate that bioluminescence imaging in MIP-Luc-VU mice provides a noninvasive means of detecting β-like cells in the liver. They also show that Mafa has a markedly intense and sustained role in β-like cell production in comparison with Mafb.